Scale dependence of fluid flow and solute transport in fracture networks of tight geological formations. - Akomolafe, Oluwaseun Joseph (Kansas State University, 2023)
Understanding the effect of fracture network heterogeneity on flow and transport is of great importance because fractures are primary pathways, particularly in tight formations with low permeability values. Although numerous studies were conducted to investigate solute transport in fractured media, simultaneous investigation of the effect of scale on flow and transport in tight reservoirs is very limited. More specifically, we are not aware of any study that has addressed how the continuous time random walk (CTRW) model parameters vary with scale. In this study, we carried out extensive numerical simulations in sparse fracture networks of sizes L = 20, 35, and 50 m under two different fracture densities (p30 = 0.05 and 0.1) using the discrete fracture network approach. The fractures in the networks were elliptical in shape, whose radii followed the truncated power-law distribution with exponent α = 1.5, 2, and 2.5. We simulated fluid flow based on the Reynolds equation and solute transport using the particle tracking approach. The solute transport behavior was quantified by fitting the CTRW model to the simulated arrival time distributions averaged over at least twenty realizations. Results showed that as the exponent α increased, the permeability of the networks decreased. We found non-Fickian solute transport behavior, deduced from small β values, in all the fracture networks studied here. We demonstrated that although the value of permeability might have reached the REV value, solute transport parameters could still be scale-dependent. Our numerical analyses disclosed the scale dependence of the CTRW model parameters on the geometrical properties and topological properties of fracture networks, confirmed through our regression analyses.
Keywords: Tight reservoirs; Solute transport; Fracture density; Scale effect; Particle tracking